Combination of tanshinone IIA and doxorubicin possesses synergism and attenuation effects on doxorubicin in the treatment of breast cancer. (3rd April 2019) - Li, Kun; Liu, Wensu; Zhao, Qian; Wu, Chunxia; Fan, Chenxing; Lai, Hong; Li, Shizheng
Abstract : Doxorubicin (Dox) is a first‐line drug for breast cancer chemotherapy. However, with the prolongation of chemotherapy cycle, breast cancer cells are increasingly tempt to resist Dox, and meanwhile, high cumulative dose of Dox brings enhancing toxic side effects, and these effects may lead to chemotherapy failure. Hence, it is necessary to search an agent in combination medication with Dox, which can not only enhance the chemosensitivity of Dox but also reduce the toxic side effects. Tanshinone IIA (Tan IIA) is reported to have antitumor activity in addition to its cardiovascular protective effects. We employed human breast cancer MCF‐7 and MCF‐7/dox cells in order to assess whether Tan IIA might perform such function. Our in vitro studies showed that Tan IIA could enhance the sensitivity of breast cancer cells to Dox through inhibiting the PTEN/AKT pathway and downregulating the expression of efflux ABC transporters including P‐gp, BCRP, and MRP1. In addition, our in vivo studies showed Tan IIA enhanced the chemotherapeutic effect of Dox against breast cancer while reducing its toxic side effects including weight loss, myelosuppression, cardiotoxicity, and nephrotoxicity. Therefore, Tan IIA could be used as a novel agent combined with Dox in breast cancer therapy.